Effectiveness of Myofascial Release Technique Versus Cupping Therapy on Pain and Range of Motion in College Going Students with Trapezitis (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: Trapezitis is one of the common inflammatory conditions seen among college going students dueto prolonged poor posture stressful neck movement. Students with Trapezitis usually complaints of pain anddifficulty in activities of daily living. Myofascial release technique can be defined as a soft tissue mobilizationtechnique that reduce trapezius spasm and ultimately pain is reduced. Cupping is ancient medical technique it is general utilise a glass cup to create suction over a painful area.Need of study: There are few literatures or research work available on this. No comparison is done on abovetechniques. So, this study was done to compare both the techniques.Objective: To compare the Myofascial Release Technique and Cupping therapy on pain intensity and neck disabilityindex in Trapezitis among college going students.Methodology: A total of 50 students with Trapezitis meeting the inclusion and exclusion criteria were allocated into two groups of 25 each. Group A (MFR) and Group B (Cupping) to receive 6 sessions of MFR and cupping therapy Pre and Post intervention scores of Visual analogue Scale (VAS), Cervical ROM (CROM) and Neck disability index (NDI) were measured.Results: Data was analysed by SPSS21, t-test were applied. Statistically significant improvements were observed in both groups but more pronounced in Group B. VAS (t = 6.3257) P
Keywords: Trigger Points, Students, Myofascial Release Technique, cupping therapy, Trapezitis.